Manufacturing method of stainless steel foil with flattening film
Patent Information
- Application Number
- JP2021083408
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-17
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2041-05-17
Smart Images

Figure 0007652619000004 
Figure 0007652619000005 
Figure 0007652619000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a stainless steel foil with a planarizing film that can be used for flexible substrates for electronic devices. [Background technology]
[0002] Stainless steel foil with a planarizing film is attracting attention as a flexible substrate for devices that require high-temperature processes. Since the surface of stainless steel foil has irregularities such as rolling lines, a coating is required to impart flatness and insulation properties in order to use it as a device substrate. Flexible substrates for devices usually require heat resistance, flatness, and insulation reliability, so stainless steel foil coated with a silica-based inorganic-organic hybrid material, which has superior heat resistance compared to resin-based varnishes and films, is a promising material.
[0003] Silica-based inorganic-organic hybrid materials generally consist of R 2 Si(OR') 2 , RSi(OR') 3 , or Si(OR') 4 The polymer has a structure containing the compound, and can be obtained by applying a coating solution obtained by hydrolysis and condensation in a solvent and then subjecting it to heat treatment. Here, R is any organic group, and R' is an alkyl group. R 2 Si(OR') 2 , RSi(OR') 3 , Si(OR') 4 correspond to the D nucleus (difunctional), T nucleus (trifunctional), and Q nucleus (tetrafunctional) of Si, respectively.
[0004] Stainless steel foils on which a film of a silica-based inorganic-organic hybrid material is formed are described in Patent Documents 1 to 3, etc. Patent Document 1 describes a stainless steel foil coated with an inorganic-organic hybrid film that is excellent in heat resistance, workability, flatness, flexibility, and insulation. This stainless steel foil is obtained by coating one or both sides of a stainless steel foil substrate with an inorganic-organic hybrid film containing an appropriate amount of organic groups produced using a sol-gel method, resulting in a stainless steel foil with excellent heat resistance, workability, flatness, insulation, etc.
[0005] Patent Document 2 describes a short-curing flattening film-forming coating liquid capable of flattening the surface of a metal foil coil to the same level as a glass substrate in a roll-to-roll process, a flattening film that is also heat-resistant and moisture-resistant, and a metal foil coil flattened thereby. This metal foil coil is obtained by applying a short-curing flattening film-forming coating liquid obtained by adding 0.1 to 1 mol of acetic acid and 0.005 to 0.05 mol of organotin as catalysts to 1 mol of phenyltrialkoxysilane in an organic solvent, hydrolyzing the mixture with 2 to 4 mol of water, and then distilling off the organic solvent under reduced pressure at a temperature of 160°C to 210°C to obtain a resin, which is then dissolved in an aromatic hydrocarbon solvent.
[0006] Patent Document 3 describes a stainless steel foil with an insulating coating for organic EL, which can form a good element without short-circuiting and without dark spots, so that when multiple organic EL light-emitting elements are formed on a substrate, each element can be controlled independently. This stainless steel foil is coated with a first layer and a second layer in that order, and the second layer is a phenyl-containing silica film layer with excellent smoothness and insulation. In order to suppress the generation of cracks due to scratches or foreign matter on the stainless steel foil surface during the formation of the second layer, a highly heat-resistant first layer that does not deteriorate due to heat is provided in order to mitigate the effects of large protrusions and foreign matter on the stainless steel surface. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2003-247078 A [Patent Document 2] International Publication No. 2016 / 076399 [Patent Document 3] JP 2016-000858 A Summary of the Invention [Problem to be solved by the invention]
[0008] Among devices, electronic devices that stack upper and lower electrodes and thin films of various semiconductor layers, such as solar cells, organic electroluminescence (EL) lighting, and batteries, require high flatness in the coated stainless steel foil because unevenness in the substrate can cause disturbances in the stacked structure and reduce manufacturing yields. Such electronic devices are exposed to high temperatures of over 400°C during the device manufacturing process, and performance is reduced if there is outgassing from the substrate during device layer deposition, so flatness must be improved by using a coating made of a highly heat-resistant silica-based inorganic-organic hybrid material.
[0009] In order to improve the flatness of the stainless steel foil with the film, measures have been taken such as cleaning the surface of the stainless steel foil, forming a thick film as much as possible, and forming the film in a clean environment to prevent the inclusion of foreign matter during the formation of the flattening film. However, even with the flattening film-coated stainless steel foil manufactured by taking the above measures, there is a problem that the manufacturing yield of electronic devices varies greatly. The "yield" used in this specification means that for devices manufactured from one roll of stainless steel foil with a flattening film, the yield = (number of devices that meet the performance standard / total number of devices manufactured) x 100%. The meaning of "large variation in manufacturing yield" refers to the fact that the manufacturing yield when the same device is manufactured depending on the lot of the stainless steel foil roll with the flattening film varies greatly. From an industrial perspective, it is desirable to obtain a high manufacturing yield regardless of the lot of the stainless steel foil roll with the flattening film. [Means for solving the problem]
[0010] The inventors prototyped an organic EL lighting panel, which has the most stringent specifications of any electronic device, and investigated defects in stainless steel foil with a planarizing film and the organic EL lighting panel.As a result, they discovered that the cause of defects in electronic devices originates from overhanging depressions of a specific shape and size that are present on the surface of the stainless steel foil.They selected stainless steel foil rolls with a low number density of specific overhanging depressions, and found that stainless steel foil rolls with a planarizing film manufactured using the selected stainless steel foil rolls had small variation in electronic device manufacturing yields between lots of stainless steel foil rolls with a planarizing film, and all showed high manufacturing yields.
[0011] Electronic devices may be manufactured using a roll of stainless steel foil with a flattening film in a roll to roll process, cut into device size, and their performance examined to determine the yield, or they may be manufactured by cutting a roll of stainless steel foil with a flattening film to a size such as G2 and attaching it to a glass substrate, then manufacturing using a sheet to sheet process, peeling it off from the glass substrate and cutting it into device size, and their performance examined to determine the yield. In the present invention, the variation in the latter yield is also measured in units of stainless steel foil rolls with flattening film, not in units of cut sheet size.
[0012] The present invention provides the following: (1) A part of a stainless steel foil roll is used as a test piece, and a phenylsiloxane polymer film having a thickness of 2.0 μm or more and 4.0 μm or less is formed on the stainless steel foil surface of the test piece, The phenylsiloxane polymer film is immersed in a liquid having a conductivity of 0.1 S / m or more and 100 S / m or less over an area of 4 mm 2 More than 9mm 2 The following electrode was placed on the test piece as the upper electrode, the stainless steel foil was placed on the test piece as the lower electrode, and the surface of the test piece was scanned with the upper electrode. When 10 V was applied between the upper electrode and the lower electrode, the leakage current was 1 μA / mm 2 Count the number of points that are equal to or greater than ... The leakage current is 1 μA / mm 2 The number of points that are equal to or greater than 100 cm 2Selecting stainless steel foil rolls having 10 or less pieces per roll, A method for producing stainless steel foil with a planarizing film, comprising forming a silica-based inorganic-organic hybrid film on at least one surface of the stainless steel foil of the selected stainless steel foil roll. (2) The method for producing a stainless steel foil with a planarizing film according to (1) above, wherein the Si nuclei constituting the silica-based inorganic-organic hybrid film contain only T nuclei and Q nuclei. (3) For the Si cores constituting the silica-based inorganic-organic hybrid film Q The method for producing a stainless steel foil with a flattened film according to (2) above, wherein the ratio of the cores is 70% or less. (4) The method for producing a stainless steel foil with a planarizing film according to any one of (1) to (3), wherein the silica-based inorganic-organic hybrid film has a thickness of 0.3 μm or more and 5.0 μm or less. Effect of the Invention
[0013] The manufacturing yield of electronic devices manufactured using the stainless steel foil with the planarizing film as a substrate can be increased and the variation in yield can be reduced. [Brief description of the drawings]
[0014] [Figure 1] Schematic diagram showing a cross section of a dent defect in stainless steel foil. [Diagram 2] A cross-sectional photograph of irregularities equivalent to rolling marks that do not lead to device defects. [Diagram 3] A cross-sectional photograph of unevenness that can lead to device failure. [Figure 4] Schematic diagram for explaining a method for measuring a leakage current and an applied voltage. [Diagram 5] A photo showing defects on a stainless steel surface. [Figure 6] A diagram showing how to calculate the angles α1 and α2 of the recesses. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] [Identifying causes of device failure] The dent defects of stainless steel foil that lead to electronic device failure will be explained using Figure 1. Figure 1 is a schematic diagram of a cross section of a dent defect on the surface of stainless steel foil in a direction perpendicular to the rolling direction. A surface dent of stainless steel foil that leads to device failure (hereinafter also simply referred to as a "dent defect") has at least one of the angles α1 and α2 between the surface of the stainless steel foil and the wall surface of the dent being 100 degrees or less. This shape is called an overhang. Also, when viewed from above, the width of the dent in a direction perpendicular to the rolling direction is 5.0 μm or more. If there is an overhang or a dent defect with a shape similar to that, the wall surface of the dent cannot be sufficiently covered with the planarizing film, or even if it can be covered, the silica-based inorganic-organic hybrid film composed only of T nuclei and Q nuclei of Si is hard and has low toughness, so that cracks occur due to film stress at the edge of the dent. As a result, a short circuit occurs between the electrode of the electronic device formed on the planarizing film and the stainless steel foil, or a part of the layer that constitutes the electronic device is broken, causing the electronic device to fail.
[0016] When both angles α1 and α2 exceed 100 degrees, the planarizing film-forming coating solution fills the recesses, and the film stress generated at the edge of the recesses is not high enough to cause cracks in the planarizing film, so in this case, it does not lead to device failure. Since the recesses are formed when inclusions in the stainless steel fall off during rolling, if the width of the recess in the direction perpendicular to the rolling direction is less than 5.0 μm, the recess is caused by small inclusions. This makes the recesses shallower, making it easier for the planarizing film to cover the recesses, and stress is less likely to concentrate on the edges, so it does not lead to device failure.
[0017] [Method of detecting overhang or similarly shaped dent defects] It is presumed that overhangs or dent defects with a similar shape are caused by inclusions such as spinel contained in stainless steel falling off during the rolling process. The shape of the dents after falling off varies depending on the size and shape of the inclusions. In addition, the surface of stainless steel foil has many irregularities such as rolling lines. For this reason, it is not realistic to find overhangs or dent defects with a similar shape by optically observing the stainless steel foil itself or monitoring the surface shape. The inventors have discovered a method for detecting overhangs or dent defects with a similar shape that can lead to device failures by forming a phenylsiloxane polymer film on the stainless steel foil and then using a conductive liquid to examine the leakage current between the stainless steel foil.
[0018] Conventionally, the leakage current of stainless steel foil with flattening film was measured by forming an upper electrode by depositing electrode materials such as Al, Cu, and Pt on the flattening film by a dry process such as vapor deposition and sputtering, using stainless steel foil as the lower electrode, and applying a voltage between the upper and lower electrodes. The applied voltage is usually 10 to 100 V. To find the defective part that leads to the current leakage, it is desirable to form many small upper electrodes and measure the leakage current between each upper electrode and the stainless steel foil in sequence, but a size of about 1 mmφ is required to measure while ensuring the connection between the upper electrode and the terminal using conductive paste. In addition, a space of nearly 1 mm is required between the upper electrodes. Therefore, the area where the leakage current can be measured is essentially about half of the entire stainless steel foil with flattening film. Furthermore, even if the leakage part is observed with an optical microscope or SEM (scanning electron microscope) to investigate the cause of the leakage, it is not possible to determine where the defect is in the 1 mmφ upper electrode because an opaque metal electrode is formed. In this method, in which a metal electrode is formed as the upper electrode and the leakage current is measured, a large leakage current tends to suddenly begin to flow at a relatively high voltage of 50 V or more. When the leakage current flows, the electrode material migrates and the phenylsiloxane polymer film undergoes dielectric breakdown, which makes it difficult to know the shape of the stainless steel foil and the planarization film before dielectric breakdown.
[0019] In response to this, the inventors discovered a method to examine the leakage current by scanning the planarized film while applying a voltage between a stainless steel foil and a conductive liquid held on a small sponge or other tip as the upper electrode (hereinafter referred to as the "probe"). Figure 4 is a schematic diagram showing this method. "PC" in Figure 4 is a computer used for measurement. 1 represents the probe containing the conductive liquid and the electrode rod to which the electrode cable is fixed, and is attached to the XY motorized stage. 2 is the probe containing the conductive liquid, 3 is the phenylsiloxane polymer film, and 4 is the electrode cable.
[0020] A part of the phenylsiloxane polymer film 1 is scraped off and placed on the inspection table. One of the electrode cables 4 is fixed to the stainless steel foil with conductive paste, and the other is connected to the probe 2 immersed in conductive liquid, and set as shown in Figure 4. The two electrode cables are connected to a constant voltage power supply capable of measuring minute currents, such as Keithley Source Measure Unit 236 from Keithley Instruments, and a voltage of 10 V is applied and the current at that time is measured. The probe 2 is fixed to the XY stage and scans the entire surface of the phenylsiloxane polymer film 3 from one end to the other. If the power supply is connected to a PC and the XY stage is made motorized, the number density of dent defects can be automatically measured. If dent defects can be found by detecting a weak current with a low applied voltage by this operation, the shape of the stainless steel foil before insulation breakdown can be grasped. When the phenylsiloxane polymer film is formed to a thickness of 3.0 ± 1.0 μm, dents that lead to device defects can be easily detected by the leakage current per unit area. The leakage current per unit area is the minute current detected when a voltage is applied divided by the electrode area at the time of measurement. In the present invention, the electrode area is the area where the tip of a tip such as a sponge soaked in a conductive liquid contacts the membrane. Hereafter in this specification, the leakage current per unit area will be simply referred to as leakage current.
[0021] For example, in the cross-sectional photograph of Figure 2, where there are irregularities corresponding to rolling streaks that do not lead to device defects, the leakage current when 10 V is applied is 1 nA / mm2 In addition, in the area where there is a dent defect that leads to device failure, as shown in the cross-sectional photograph in Figure 3, the leakage current is 1 μA / mm 2 The phenylsiloxane polymer film has good embedding properties due to its thermoplasticity, and because the film is relatively brittle, it is likely that cracks will occur in dent defects with an overhang shape, which is why it was possible to detect dent defects close to overhangs with high sensitivity.
[0022] When the thickness of the phenylsiloxane polymer film is less than 2.0 μm, the current is only a few hundred nA / mm2 even in areas with unevenness such as the rolling marks in the foil or the unevenness caused by inclusions in the foil, as shown in Figure 2. 2 This shows a leakage current of 1 μA / mm, making it somewhat difficult to distinguish it from the dent defect in Figure 3. If the film thickness exceeds 4.0 μm, the film formation stress during hardening of the phenylsiloxane polymer film increases, making it easier for cracks to occur even in places such as dents and protrusions that are not related to device failure. 2 However, since defects unrelated to device failures may be included among the defects at locations where leakage currents of up to 10000000 are detected, the detection accuracy tends to decrease.
[0023] Cracks occurred in the phenylsiloxane polymer with a thickness of 3.0±1.0 μm, and the current density was 1 μA / mm 2 The dents from which the above leakage currents were detected had at least one of the angles α1 and α2 between the stainless steel foil and the dent being 100 degrees or less, and had a width perpendicular to the rolling direction of 5.0 μm or more.
[0024] At this time, the angles α1 and α2 between the stainless steel foil and the recess were measured as follows. When the locations where a leakage current of 1μA or more was detected were marked and observed with an optical microscope, a defect like A-1 in Figure 5 was found. When this defect was observed with an SEM, it was confirmed that it extended in the rolling direction as A-2 in Figure 5. A cross section of the center was created by FIB (Focused Ion Beam) processing, and a cross-sectional photograph, A-3 in Figure 6, was taken with an SEM. Since dents are usually asymmetric, the dent is divided into thirds in the width direction, and when calculating α1, an ellipse is drawn that approximates the left end of the dent in the stainless steel foil to 1 / 3 of the width. Next, a tangent to the ellipse is drawn at the intersection of the ellipse and a straight line that approximates the stainless steel foil in a location where there is no dent. The angle between the two straight lines is α1. Similarly, α2 can be calculated by drawing an ellipse that approximates the right end of the dent to 1 / 3 of the width.
[0025] Therefore, instead of fabricating an electronic device, a phenylsiloxane polymer film was formed on a stainless steel foil with a thickness of 3.0 ± 1.0 μm, and a conductive liquid was used to measure the leakage current of 1 μA / mm at an applied voltage of 10 V. 2 It was found that by searching for points where this value is exceeded, it is possible to determine the density of defects that could lead to device failure.
[0026] The dent defects that lead to device failures revealed in this way had the following characteristics. The dents are caused by inclusions falling off during the rolling process, so they are long in the rolling direction. -Dent width: 5.0~15.0μm. Length: 15.0~70.0μm. Depth: 2.5.0μm or more.
[0027] [Causes of dent defects] Dent defects close to overhangs that lead to device failures are formed when inclusions in the stainless steel fall off during rolling or are embedded in the foil. For this reason, it is believed that the number of dent defects with overhanging cross sections can be reduced by first producing foil by rolling stainless steel with fewer inclusions.
[0028] Various methods have been studied to reduce the number of inclusions in the stainless steel, which is the base material for manufacturing stainless steel foil. However, there are problems such as increased process costs and difficulty in removing inclusions depending on the type of steel. The inventors have found a simple method to find dent defects with ends close to overhangs, which will be described below, and used this method to investigate the distribution of dents with ends close to overhangs. As a result, they found that there are stainless steel foils that do not lead to device failure and have an acceptable number density of dent defects, even if stainless steel foil is manufactured using a base material in which inclusions in the stainless steel have not been removed by a special method during the rolling process. Furthermore, it was found that the variation in number density is limited to about ±15% in a single stainless steel foil roll cut to a standard size of 300 m in length and 0.5 m in width, but the variation is several times greater between different rolls. The number density on the outer and inner surfaces of the foil roll is almost the same in a single stainless steel foil roll. This is thought to be because the amount of inclusions present does not change on the outer and inner surfaces of the foil roll during the process of rolling the foil.
[0029] Specifically, a simple method for finding dent defects close to overhangs is as follows: (1) First, cut off a portion of the end of the stainless steel foil roll used to apply the planarizing film, and cut out four 120 mm square test pieces. (2) In a clean room, spin coat the surface with phenylsiloxane polymer to a thickness of 3.0 ± 1.0 μm, dry, and heat treat to form a film. (3) In a clean room, scan the film surface using a microprobe immersed in a liquid (such as saline) with a conductivity of 0.1 S / m or more. (4) Check that the leakage current is 1 μA / mm when a voltage of 10 V is applied. 2 The above points were judged to be dent defects. After that, when the cross section of this part was examined with FIB-SEM, it was found that almost all of the defects were dent defects with cross sections close to overhangs.
[0030] The number density of dent defects close to the overhang was investigated using the method described above. As a result, the number density of dent defects close to the overhang was 100 cm 2When various silica-based inorganic-organic hybrid films were formed on stainless steel foil rolls with a flattening film to produce stainless steel foil, the yield of electronic devices was improved regardless of which silica-based inorganic-organic hybrid film was formed. 2 When four or less pieces of stainless steel foil were used per unit area, the yield was further improved and the variation was further reduced.
[0031] The method for producing the planarizing film-coated stainless steel foil of the present invention will be described. [Stainless steel foil roll sorting process] The type of steel for the stainless steel foil of the present invention may be either ferritic or austenitic. There is no particular limit to the thickness, but for flexible substrates for devices, the thickness is generally 8 μm or more and 100 μm or less. The particularly desirable range of the stainless steel foil thickness is 10 μm or more and 50 μm or less. The end of the stainless steel foil roll is partially cut to cut out four test pieces of 120 mm square. Phenylsiloxane polymer is applied to the surface of the test piece, then dried and heat treated to form a film with a thickness of 2.0 μm to 4.0 μm, and a test piece for measuring leakage current is prepared. Application can be performed by a method such as spin coating or bar coating. In the case of spin coating, the film thickness can be adjusted by the rotation speed, and in the case of bar coating, the film thickness can be adjusted by the bar number. Drying is performed in an oven at 70 to 110 ° C for 1 minute, and heat treatment is performed in an inert gas atmosphere, such as a nitrogen atmosphere, using a clean oven at 350 to 450 ° C for 2 to 60 minutes. It is possible to form a film other than phenylsiloxane polymer as a test piece for measuring leakage current, for example, a film made from the hydrolysis and condensation reaction product of tetramethoxysilane or a polyimide film, but phenylsiloxane polymer is used because it is possible to form a relatively thick film and because it is thermoplastic, it can fill the depressions in the stainless steel foil surface without cracking and therefore can completely fill in the gaps.
[0032] When the area is immersed in a liquid with a conductivity of 0.1 S / m or more and 100 S / m or less, it is 4 mm2 More than 9mm 2 The following probes are explained. Whether the probe is sufficiently immersed in a liquid with a conductivity of 0.1 S / m to 100 S / m can be judged by whether or not conduction can be confirmed when the probe is pressed against the stainless steel foil in Figure 4. The liquid is soaked into a sponge or the like inside the probe to the extent that the liquid does not seep or drip from the probe when pressed. The conductive liquid is soaked into a sponge, a cotton swab, foamed urethane, or other porous and flexible material. The reason for using a porous and flexible material is to prevent damage to the film surface during sweeping. Since it is difficult to hold a porous and flexible material as it is, it is inserted into a thin cylindrical insulating tube, and an electrode cable is inserted from the other side of the tube to make contact with the porous and flexible material soaked in the conductive liquid to form a probe. The conductive liquid is covered by a tube, so there is no problem with the liquid running out during measurement due to evaporation, etc. The guideline for the number density of defects is an average of 10 cm 2 Since the density is low at 1 per electrode, slight differences in the size of the electrode area do not affect the calculation of the number density. As the conductive liquid, in addition to saline water, an aqueous solution of KCl, dilute hydrochloric acid, etc. can be used. When the area is immersed in a liquid with a conductivity of 0.1 S / m or more and 100 S / m or less, it is 4 mm 2 More than 9mm 2 The surface of the test piece was scanned using the following probe, and the current was 1 μA / mm when a voltage of 10 V was applied. 2 Mark the leak points where the flow is greater than or equal to 100 cm. 2 The stainless steel foil roll having 10 or less particles per 100 cm is selected as acceptable and used in the next manufacturing process of the stainless steel foil with flattened film of the present invention. 2 The reason why a sample with 10 or less particles per square was deemed acceptable is that, as mentioned above, various silica-based inorganic-organic hybrid films were then formed to produce stainless steel foils with planarized films, and electronic devices were then manufactured. As a result, the manufacturing yield of the electronic devices improved compared to conventional methods, and the variation in the manufacturing yield decreased.
[0033] [Phenylsiloxane polymer film forming coating solution] The phenylsiloxane polymer film used in detecting dent defects can be produced by various methods. For example, it is formed from the coating liquid shown below. This coating solution is prepared by adding 0.1 to 1 mol of acetic acid and 0.005 to 0.05 mol of organotin as catalysts to 1 mol of phenyltrialkoxysilane in an organic solvent, and hydrolyzing with 2.0 to 4.0 mol of water.Then, the organic solvent used in the hydrolysis of the phenyltrialkoxysilane, and the water and alcohol as reaction by-products are distilled off under reduced pressure at a temperature of 160°C to 210°C, to obtain a resin, which is then dissolved in an aromatic hydrocarbon solvent.
[0034] Examples of the phenyltrialkoxysilane include phenyltrimethoxysilane, phenyltriethoxysilane, and phenyltripoxysilane.
[0035] Examples of organic solvents that can be used when hydrolyzing phenyltrialkoxysilane include methanol, ethanol, and propanol.
[0036] Examples of aromatic hydrocarbon solvents include toluene, xylene, etc. Other organic solvents may be mixed with the aromatic hydrocarbon solvents as long as the mixture does not affect the properties.
[0037] The thickness of the phenylsiloxane polymer film is 2.0 μm or more and 4.0 μm or less. If the film thickness is thinner than 2.0 μm, it will not be able to completely cover the irregularities on the stainless steel foil surface. If the film thickness exceeds 4.0 μm, the film will be more likely to crack. The thickness of the phenylsiloxane polymer film can be determined by measuring the thickness of the stainless steel foil before and after film formation with a contact thickness gauge and calculating the difference.
[0038] The phenylsiloxane polymer film is cured at a heat treatment temperature of 300°C to 450°C in an inert gas atmosphere, and then a leak current is measured using a conductive liquid as a probe to detect dent defects. This phenylsiloxane polymer film is a type of silica-based inorganic-organic hybrid film, and can also be used as a planarizing film, which will be described later. In this case, the composition of the planarizing film is 100% T nuclei to which phenyl groups are bonded.
[0039] [Manufacturing process of stainless steel foil with flattening film] A silica-based inorganic-organic hybrid film is formed on the surface of the stainless steel foil of the selected stainless steel foil roll, preferably to a thickness of 0.3 μm or more and 5.0 μm or less. The silica-based inorganic-organic hybrid film may be formed on either side of the selected stainless steel foil roll. It may also be formed on both sides. When forming on both sides, one side may be coated and then heat-treated to form a silica-based inorganic-organic hybrid film on one side, and then the other side may be coated and heat-treated. Alternatively, both sides may be coated simultaneously using a dip coater or the like, and then heat-treated simultaneously on both sides.
[0040] [Silica-based inorganic-organic hybrid film] Silica-based inorganic-organic hybrid films generally consist of silicone units, R 2 Si(OR') 2 , RSi(OR') 3 , or Si(OR') 4 The polymer has a structure containing the compound, and can be obtained by applying a coating solution obtained by hydrolysis and condensation in a solvent and then subjecting it to heat treatment. Here, R is any organic group, and R' is an alkyl group. R 2 Si(OR') 2 , RSi(OR') 3 , Si(OR') 4 correspond to the D nucleus (difunctional), T nucleus (trifunctional), and Q nucleus (tetrafunctional) of Si, respectively.
[0041] When the silica-based inorganic-organic hybrid film constituting the planarization film contains a D nucleus of Si as a component, it can impart flexibility to the film, but during the high-temperature process of device fabrication, the D nucleus forms a three-membered ring and is removed, which adversely affects the characteristics of the device. For this reason, the planarization film is required to be a silica-based inorganic-organic hybrid film composed only of T and Q nuclei of Si. The ratio of Q nuclei to all Si nuclei is 70% or less. If the Q nuclei exceed 70%, the density of the Si-O bonds constituting the film becomes too high, making the film prone to cracking, which is unsuitable. The T nucleus has one organic group directly bonded to Si, which can impart flexibility to the film. A more preferable range of Q nuclei is 10% or more and 55% or less.
[0042] As the organic group R directly bonded to Si, a methyl group or a phenyl group is preferable from the viewpoint of heat resistance. The methyl group and the phenyl group may be contained alone or both may be contained simultaneously. The type and amount of Si nuclei in the planarization film can be identified by 29Si-NMR measurement. The organic group directly bonded to Si can be investigated by FTIR or a combination of 13C-NMR and 1H-NMR.
[0043] [Silica-based inorganic-organic hybrid film forming coating solution] The silica-based inorganic-organic hybrid film can be prepared by various methods. When the silica-based inorganic-organic hybrid film is a phenyl group-modified silica film, it is prepared, for example, from the coating liquid shown below.
[0044] This coating liquid is prepared by adding 0.1 to 1 mol of acetic acid and 0.005 to 0.05 mol of organotin as catalysts to 1 mol of phenyltrialkoxysilane in an organic solvent, hydrolyzing the phenyltrialkoxysilane with 2.0 to 4.0 mol of water, and then distilling off the organic solvent used in the hydrolysis of the phenyltrialkoxysilane, as well as water and alcohol as reaction by-products, under reduced pressure at a temperature of 160°C to 210°C, to obtain a resin, which is then dissolved in an aromatic hydrocarbon solvent.
[0045] Examples of the phenyltrialkoxysilane used herein include phenyltrimethoxysilane, phenyltriethoxysilane, and phenyltripoxysilane.
[0046] Examples of organic solvents that can be used when hydrolyzing phenyltrialkoxysilane include methanol, ethanol, and propanol.
[0047] The organic solvent distilled off during vacuum distillation includes the organic solvent used to hydrolyze the phenyltrialkoxysilane, as well as alcohol produced by hydrolysis of the phenyltrialkoxysilane, and may also include water produced in the condensation reaction of the hydrolyzed phenyltrialkoxysilane.
[0048] Examples of aromatic hydrocarbon solvents include toluene, xylene, etc. Other organic solvents may be mixed with the aromatic hydrocarbon solvents as long as the mixture does not affect the properties.
[0049] Organotin is a catalyst that promotes the polycondensation reaction of phenyltrialkoxysilane and its hydrolysis condensation reaction product, and phenyl group-containing ladder polymer. Organotin includes dibutyltin diacetate, bis(acetoxydibutyltin) oxide, dibutyltin bisacetylacetonate, dibutyltin bismaleic acid monobutyl ester, dioctyltin bismaleic acid monobutyl ester, bis(lauroxydibutyltin) oxide, etc.
[0050] The silica-based inorganic-organic hybrid film is formed by applying the above-mentioned coating liquid to the surface of the stainless steel foil of a selected stainless steel foil roll and curing it at a heat treatment temperature of 300°C to 450°C in an inert gas atmosphere, preferably to a film thickness of 0.3 μm to 5.0 μm.
[0051] When the silica-based inorganic-organic hybrid film is a methyl group-modified silica film, it is prepared from, for example, the coating liquid shown below. 0.6 mol of methyltriethoxysilane and 0.4 mol of tetramethoxysilane are hydrolyzed and condensed in 12 mol of ethanol with 2 mol of water and 0.1 mol of acetic acid, and the resulting coating solution is applied to a stainless steel foil with a thickness of 1.0 μm. After coating, the film is heat-treated in nitrogen at 450°C for 10 minutes, resulting in a film with 60% T nuclei with methyl groups bonded and 40% Q nuclei. In addition to tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, colloidal silica, etc. can be used as the raw material for the Q nuclei. In addition to methyltriethoxysilane, methyltrimethoxysilane can also be used. These raw materials may be combined in combination.
[0052] In silica-based inorganic-organic hybrid films, the organic group of the raw material organoalkoxysilane may thermally decompose, and Si may change from T nuclei to Q nuclei, depending on the heat treatment temperature after coating and the gas atmosphere during the heat treatment. Therefore, when a coating solution obtained by hydrolyzing and condensing a raw material with T nuclei, for example 1 mole of methyltrimethoxysilane, in 8 moles of methanol with 3 moles of water and 0.01 moles of nitric acid is applied to a thickness of 0.4 μm and then heat-treated at 500°C for 1 minute in nitrogen containing 0.1% oxygen, 98% of the Si in the planarized film is T nuclei with methyl groups bonded, and 2% is Q nuclei with methyl groups thermally decomposed. On the other hand, when the coating solution is applied to a stainless steel foil with a thickness of 0.4 μm and then heat-treated at 500°C for 1 minute in nitrogen, the Si in the T nuclei with methyl groups bonded becomes 100%.
[0053] Next, the stainless steel foil with flattening film produced by the manufacturing method of the present invention will be described. The stainless steel foil with flattening film is the stainless steel foil selected by the above-mentioned stainless steel foil roll selection process. Therefore, this stainless steel foil has 100 cm2 of recesses, in which the angle between the stainless steel foil surface and the wall surface of the recess is 100 degrees or less, and the width of the recess in the direction perpendicular to the rolling direction is 5.0 μm or more, as shown in FIG. 2 There are 10 or less per prize.
[0054] The density of the number of recesses in which the angle between the surface of the stainless steel foil and the wall of the recess is 100 degrees or less on the surface of the stainless steel foil with the flattening film of the invention can be determined after the flattening film is formed by the following method. 2 The stainless steel foil with the planarizing film is cut into 2 mm squares and embedded in resin, and the cut surface perpendicular to the rolling direction is polished by CMP (Chemical Mechanical Polishing) and observed by SEM. The angles (α1, α2) of the recesses in the stainless steel foil are measured using the method described above, and the width of the recesses in the direction perpendicular to the rolling direction can also be measured. The number density of the recesses can be determined by counting the recesses with an angle of 100 degrees or less and a width of 5.0 μm or more. To determine the number density more accurately, the area of the stainless steel foil with the planarizing film to be inspected is increased.
[0055] The thickness of the silica-based inorganic-organic hybrid film formed on the stainless steel foil is preferably 0.3 μm or more and 5.0 μm or less. If it is thinner than 0.3 μm, the coverage of the stainless steel foil surface will be insufficient, causing a short circuit between the stainless steel foil and the device, or the surface of the inorganic-organic hybrid film will not be sufficiently smooth, causing delamination of the electrode layer and semiconductor layer constituting the device, which is unsuitable. If it exceeds 5.0 μm, the film will be prone to cracking. Not only will cracks easily occur during film formation, but the film will also be prone to cracking when the stainless steel foil coated with the flattening film is bent as a flexible substrate. It is even more preferable that the film thickness is 0.5 μm or more and 3.5 μm or less from the viewpoint of uneven coverage and crack prevention. EXAMPLES
[0056] The present invention will now be further described with reference to examples, although it should be understood that the present invention is not limited to the examples presented herein.
[0057] [Manufacturing test of stainless steel foil with flattening film 1] In test 1, 20 rolls of stainless steel foil made of SUS304 steel and 20 μm thick, each roll being 330 mm wide and 300 m long, were prepared. The test was carried out on a group of 5 rolls randomly selected from these 20 rolls as Comparative Example 1, and on the remaining 15 rolls as Example 1, the selection method according to the present invention was carried out to select the rolls having an angle of 100 degrees or less between the surface of the selected stainless steel foil and the wall surface of the recess on the surface, a width of 5.0 μm or more in the direction perpendicular to the rolling direction of the recess, and a number of the recesses of 100 cm or less. 2 The test was carried out on two groups of five stainless steel foil rolls, each containing 10 or less pieces. The lot numbers of the five rolls in the example were assigned as Good-1 to Good-5. The lot numbers of the five rolls in the comparative example were assigned as Comparison-1 to Comparison-5.
[0058] The five rolls of Example 1 (Good-1 to Good-5) were selected as follows. First, a coating solution for forming a phenylsiloxane polymer film was prepared. Using a 1L flask, the raw materials were mixed to have the compounding ratio shown in Table 1, and the total amount was 0.7L. After mixing, the raw materials were stirred and mixed with a magnetic stirrer for 15 minutes, and refluxed under nitrogen gas flow at 80°C for 3 hours to promote hydrolysis. Then, using a rotary evaporator, the set temperature of the oil bath was set to 80°C, and the solvent was distilled under reduced pressure to obtain a condensation reaction product. Then, toluene was added in an amount equal to the weight of the condensation reaction product to dissolve the condensation reaction product. This 1L flask was connected to a reflux condenser with a Dean-Stark trap, and heating was performed under reflux. The set temperature of the oil bath and the reflux time during heating and reflux are shown in Table 1. After heating and refluxing, toluene was further added to dilute the solid concentration to 30% by mass, and a filter with a pore size of 5 μm was set and filtered under reduced pressure to obtain a coating solution for forming a phenylsiloxane polymer.
[0059] [Table 1]
[0060] Next, the end of the stainless steel foil roll used for coating the flattening film was cut to obtain four 120 mm square test pieces. In a clean room, phenylsiloxane polymer was spin-coated onto the surface to a thickness of 3.0 μm, dried in an oven at 80°C for 1 minute, and then heat-treated in a clean oven at 400°C in a nitrogen atmosphere for 10 minutes to form a film.
[0061] A 2mm square microprobe immersed in a liquid (saline) with a conductivity of 0.1 S / m or more was set on an XY stage in a clean room and used as the upper electrode to scan the film surface. A portion of the phenylsiloxane polymer film was scraped off to expose the stainless steel foil, and the electrode cable for the lower electrode was fixed to the stainless steel foil using silver paste. The cables for the upper and lower electrodes were connected to a KEITHLEY Source Measure Unit 237, and the leakage current when 10 V was applied was measured for each 2mm square area, which was the size of the probe.
[0062] The entire 100mm square area in the center of a 120mm square board was scanned, and the leakage current was 1μA / mm 2 The number of points where the density was above 1 μA / mm was calculated. The average value for all four test pieces was calculated as the density per 10 cm square shown in Table 2. 2 The number of measurement points where a leakage current of 1μA / mm or more was detected is shown in the column. 2 When the areas where the above leakage current was detected were observed with an optical microscope, defects in the stainless steel foil were found through the phenylsiloxane polymer film. All defects had a length of 5.0 μm or more in the rolling direction. Furthermore, when the cross section was observed with a FIB-SEM, overhanging dent defects were found in the stainless steel foil. For some samples, the area containing the defect was cut and embedded in resin, and CMP polishing was used to confirm the presence of overhanging depressions in the stainless steel foil. In most cases, there was only one dent defect within a 2 mm square area. During the above selection process, it was found that some samples had a high density of dent defects, exceeding several tens, and that multiple dent defects existed. 1 μA / mm 2Products with 10 or fewer leak currents were deemed to be good products, and the lot numbers were recorded as Good-1, Good-2, Good-3, Good-4, Good-5, etc. Products with more than 10 leak currents were recorded as Bad-1, Bad-2, Bad-3, Bad-4, etc. When the ninth stainless steel foil roll was examined, five lots of good products were collected. The four bad lots obtained during this screening process were used as reference examples for further testing.
[0063] [Flattening film coating] For the stainless steel foil rolls of these Examples, Comparative Examples, and Reference Examples, a phenylsiloxane polymer film was formed as a silica-based inorganic-organic hybrid film with a film thickness of 3.5 μm using a die coater. The drying furnace was set to a furnace length of 3 m and a furnace temperature of 100 ° C., and transported at a speed of 5 mpm, and wound up while attaching a slightly adhesive protective film of PAC3J-30H. Next, while peeling off the protective film, the roll was passed through a hot air drying furnace in a nitrogen atmosphere with a furnace length of 6 m and a furnace temperature of 400 ° C. at a transport speed of 1 mpm, and wound up while attaching a slightly adhesive protective film of PAC3J-30H, to obtain a stainless steel foil roll with a flattened film.
[0064] It was confirmed by 29Si-NMR that all of the Si nuclei were T nuclei. It was confirmed by FTIR that the organic groups were phenyl groups. In all of the Examples, Comparative Examples, and Reference Examples, no cracks or repelling were observed by visual observation, and the appearance was good.
[0065] The stainless steel foil rolls with the planarizing film were obtained in lengths of nearly 300 m, which were then divided into three zones in the length direction, i.e., the outer, central, and inner parts of the roll, and 10 50 mm square substrates were cut out from each zone. The 50 mm square substrates were attached to glass plates of the same size and 0.7 mm thick with a weak adhesive sheet, and the Ag(100) / MoO 3 (5) / αNPD(140) / Alq 3An organic EL device was formed with a composition of (30) / DPB:Liq(45) / Al(1.5) / Ag(25) and sealed with a glass cap. The numbers in parentheses for the device composition indicate the film thickness, in nm. The size of the device's light-emitting area is 32 mm square. αNPD, Alq 3 , DPB, and Liq are as shown below. αNPD: (Bis[N-(1-naphthyl)-N-phenyl]benzidine) Alq3: (Tris(8-hydroxyquinolinato)aluminum DPB: 1,4-dipyrenylbenzene Liq: 8-hydroxyquinolinolato-lithium
[0066] Next, 4.5 V was applied to the element to cause it to emit light, and the initial state of the light-emitting surface was visually observed and the number of black spots was counted. The percentage of the number of panels with 4 or less defects and 10 or less defects per 10 cm square to the total number of panels for each stainless steel foil roll is shown in the device characteristics column in Table 2.
[0067] For Good-1 and Good-2, 90% or more of the OLED lighting panels had four or fewer black dots per 10 cm square, indicating that devices for high-spec applications equivalent to OLED lighting panels can be manufactured with a yield of 90% or more. For Good-3, Good-4, and Good-5, the percentage of panels with four or fewer black dots per 10 cm square was lower than for Good-1 and Good-2, but was still above 50%, indicating an acceptable yield for high-spec applications equivalent to OLED lighting panels, which are difficult to manufacture. The evaluation column lists the average yield when devices for high-spec applications equivalent to OLED lighting panels were manufactured, as well as the minimum and maximum values when compared between lots.
[0068] In Example 1, the percentage of panels with 10 or less black dots per 10 cm square of organic EL lighting panels was 90% or more. If the number of black dots exceeds 4, the number of parts to be repaired in the repair process is too large, making it unsuitable for industrial production as an organic EL lighting panel or a display panel. However, for example, for solar cell applications, it may only lead to a slight decrease in conversion efficiency, and it is not a defect that is visible to customers, so 10 or less is acceptable. In addition, in the case of thin-film sensor substrates, it is only assumed that the lower electrode of the thin-film sensor and the stainless steel foil may short-circuit at the black dots. Therefore, the yield for these standard specification applications, in which defects are not directly visible to the customer, can be roughly approximated by the percentage of panels with 10 or less black dots per 10 cm square of organic EL lighting panels, and the average, minimum, and maximum yields when devices for standard specification applications are manufactured are listed in the evaluation column. For standard specification applications, if the manufacturing yield of the device is 90% or more, it is considered to be acceptable.
[0069] In Example 1, the average manufacturing yield of devices for high-spec applications was 78.2%, exceeding the target of 50%. In contrast, in Comparative Example 1, it was low at 30.4%. The manufacturing yield range was 52% to 98% in the Example, while it varied widely from 0% to 97% in the Comparative Example. Even for standard specifications, the device manufacturing yield for all lots in Example 1 was 90% or more, while in Comparative Example 1, the average value was low at 45.6%, and the yield range varied widely from 6% to 99%.
[0070] As shown in the reference example, when inspecting a stainless steel foil roll, the current was 1μA / mm per 10cm square. 2 If the number of measurement points where a leakage current of 1 μA / mm or more is detected exceeds 10, the manufacturing yield of high-spec and standard-spec devices is less than 50% and less than 90%, respectively, and the 2The manufacturing yield of each product tended to decrease as the number of measurement points where leakage current was detected increased. In the comparative example, stainless steel foil rolls were selected randomly, so the selection included defective lots such as those shown in the reference example, which is thought to have led to a decrease in yield and a large variation in yield.
[0071] [Manufacturing test of stainless steel foil with flattening film 2] Test 2 was carried out in the same manner as Test 1, except that a film containing a methyl group was formed as the planarizing film. The coating solution for forming the planarizing film was synthesized by subjecting 0.5 mol of methyltriethoxysilane and 0.5 mol of tetramethoxysilane to a hydrolysis / condensation reaction with 2 mol of water and 0.1 mol of acetic acid in 6 mol of 2-ethoxyethanol, and then adding and mixing 6 mol of MEK. A methyl group-containing silica film was formed with a film thickness of 1.1 μm using a die coater. The drying furnace had a furnace length of 3 m and a furnace temperature of 120° C., and was transported at a speed of 5 mpm, and the film was wound up while a slightly adhesive protective film of PAC3J-30H was attached. Next, the protective film was peeled off and the film was passed through a hot air drying furnace with a furnace length of 6 m and a furnace temperature of 420° C. in a nitrogen atmosphere at a transport speed of 1 mpm, and the film was wound up while a slightly adhesive protective film of PAC3J-30H was attached, to obtain a stainless steel foil roll with a flattened film. 29Si-NMR confirmed that the T nucleus and the Q nucleus were 50% each. FTIR confirmed that the organic group was a methyl group. In all of Example 2, Comparative Example 2, and Reference Examples (5 to 7), no cracks or repelling were observed by visual observation, and the appearance was good. The results of Test 2 are shown in Table 3.
[0072] In Test 2, it was also confirmed that sorting of stainless steel foil was effective in improving yield and suppressing yield variation.
[0073] [Table 2]
[0074] [Table 3] [Explanation of symbols]
[0075] PC Measurement computer 1 electrode rod 2. Probe 3. Phenylsiloxane polymer film 4 Electrode Cable
Claims
1. A part of the stainless steel foil roll is used as a test piece, and a phenylsiloxane polymer film having a thickness of 2.0 μm or more and 4.0 μm or less is formed on the stainless steel foil surface of the test piece, The phenylsiloxane polymer film is immersed in a liquid having a conductivity of 0.1 S / m or more and 100 S / m or less so that the area of the liquid is 4 mm 2 More than 9mm 2 The following electrode was placed on the test piece as the upper electrode, the stainless steel foil was placed on the test piece as the lower electrode, and the surface of the test piece was scanned with the upper electrode. When 10 V was applied between the upper electrode and the lower electrode, the leakage current was 1 μA / mm 2 Count the number of points that are equal to or greater than ... The leakage current is 1 μA / mm 2 The number of points where this is the case is 100 cm 2 Selecting stainless steel foil rolls having 10 or less pieces per roll, A method for producing stainless steel foil with a planarizing film, comprising forming a silica-based inorganic-organic hybrid film on at least one surface of the stainless steel foil of the selected stainless steel foil roll.
2. 2. The method for producing a stainless steel foil with a planarizing film according to claim 1, wherein the Si nuclei constituting the silica-based inorganic-organic hybrid film contain only T nuclei and Q nuclei.
3. 3. The method for producing a stainless steel foil with a planarizing film according to claim 2, wherein the ratio of Q nuclei to Si nuclei constituting the silica-based inorganic-organic hybrid film is 70% or less.
4. The method for producing a stainless steel foil with a flattened film according to any one of claims 1 to 3, wherein the silica-based inorganic-organic hybrid film has a film thickness of 0.3 μm or more and 5.0 μm or less.
Citation Information
Patent Citations
Inorganic-organic hybrid film-coated stainless foil
JP2003247078A
Stainless foil with film for organic el
JP2016000858A
Manufacturing method of coating liquid for film formation
JP2018123192A
Coating liquid for flatted film formation and manufacturing method therefor, metal foil coil with flatted film and manufacturing method therefor
JP2019099775A
Coating liquid for forming leveling film, and metal foil coil provided with leveling film
WO2016076399A1